Exercise training on cardiovascular diseases: Role of animal models in the elucidation of the mechanisms - Bruno Rodrigues; Daniele Jardim Feriani; Bruno Bavaresco Gambassi; Maria Claudia Irigoyen; Kátia De Angelis; Coelho Hélio José Júnior (Universidade Estadual Paulista (UNESP), 2017)
Abstract Cardiovascular diseases, which include hypertension, coronary artery disease/myocardial infarction and heart failure, are one of the major causes of disability and death worldwide. On the other hand, physical exercise acts in the preventionand treatment of these conditions. In fact, several experiments performed in human beings have demonstrated the efficiency of physical exercise to alter clinical signals observed in these diseases, such as high blood pressure and exercise intolerance. However, even if human studies demonstrated the clinical efficiency of physical exercise, most extensive mechanisms responsible for this phenomenon still have to be elucidated. In this sense, studies using animal models seem to be a good option to demonstrate such mechanisms. Therefore, the aims of the present study are describing the main pathophysiological characteristics of the animal models used in the study of cardiovascular diseases, as well as the main mechanismsassociated with the benefits of physical exercise.